2014
DOI: 10.12740/app/23103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic parameters and Framingham cardiovascular risk scores before and after in‐hospital treatment with antipsychotics

Abstract: SummaryBackground. The objective of this naturalistic study was to evaluate changes in the prevalence of metabolic syndrome (MetS) and Framingham cardiovascular risk scores in adult with schizophrenia after inhospital treatment with antipsychotics. Methods. For 58 patients (36 women and 22 men) the following data was acquired on admission and at discharge: body height and weight, waist circumference, cigarette smoking, total cholesterol, LDL cholesterol, HDL cholesterol, triglycerides (TGA), fasting plasma glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
1
4
0
8
Order By: Relevance
“…On the other hand, we observed that BMI was associated with the illness duration, being higher in those patients with fewer years of illness and SGA treatment, agreeing with other studies indicating that the critical period for developing obesity and alterations in other cardiometabolic disorder parameters is within the first 18 months of treatment [ 14 , 76 , 77 ]. In addition, we found that abdominal obesity was higher in women than in men in accordance with previous studies [ 78 ]. Regarding DBP, we showed that DBP levels were related to age, being higher in those patients with older age [ 79 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, we observed that BMI was associated with the illness duration, being higher in those patients with fewer years of illness and SGA treatment, agreeing with other studies indicating that the critical period for developing obesity and alterations in other cardiometabolic disorder parameters is within the first 18 months of treatment [ 14 , 76 , 77 ]. In addition, we found that abdominal obesity was higher in women than in men in accordance with previous studies [ 78 ]. Regarding DBP, we showed that DBP levels were related to age, being higher in those patients with older age [ 79 ].…”
Section: Discussionsupporting
confidence: 92%
“…The average HDL level was mostly high in the schizophrenia group, where the differences between diagnostic group levels were not statistically significant. For the schizophrenia group, the mean HDL level was highest (58.76 mg/dL) compared to four other studies [6,7,9,10] (45.3 mg/Dl, 49.3 mg/dL, 43.7 mg/dL, and 51.1 mg/dL, respectively). The prevalence of low HDL was the highest (65.77%) among men with unipolar depression compared to the other lipid categories, which is in contrast to the results of [6], which showed that the prevalence was 59.70% among men with bipolar depression.…”
Section: Discussionmentioning
confidence: 51%
“…The average TGA level was mostly high in the bipolar depression group compared to other groups. For the schizophrenia group, the mean TGA level was the lowest (133.10 mg/dL) compared to four other studies [6,7,10,11], which were 139.8 mg/dL, 192.4 mg/dL, 159.1 mg/dL, and 162.6 mg/dL. Also, for the schizophrenia group, the high TGA level was higher (33.20%) compared to 32.80% in [6] and lower compared to 42.30% in [12].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations